Reward for fulfillment of goals: the case of some incentives to partially state-funded Chilean universities - Wörner, Carlos H. (Education Policy Analysis Archives, 2014)
Within the framework of Chilean regulations, the state transfers different amounts of money to some universities. This transference mechanism is called the “Aporte fiscal directo” (AFD). This transference varies year-to-year according a complex verbatim mode, as expressed in the legal documents that regulates these assignations. In this note, it is explicitly shown as a mathematical algorithm that rules these transactions. Also, it is shown some predictable variations in the next year assignations according to the variation in the used parameters.